Influência da cobertura de aveia-preta e milheto sobre comunidade de plantas daninhas e produção de soja - Pereira, Renata A.; Da C. A. Alves, Pedro L. [UNESP]; Corrêa, Maria P.; De S. Dias, Tomás C. (Revista Brasileira de Ciencias Agrarias, 2011)
The success in weed control by using straw depends on the management time, straw quality and quantity. The objective of this research was to evaluate the suppressor effect of black-oats and millet straw cover on the incidence of weeds and on the productivity of the soybean crop. The experiment was carried out during the years 2006 and 2007, in an area from the Farm of Education, Research and Production of FCAV-UNESP, Jaboticabal Campus, in a completely randomized block design, with four replications. Treatments consisted of different types of black oats and pearl millet straw management before soybean seeding (without management, obtained by machine cut, desiccated using glyphosate desiccation and with paraquat) and different periods of straw deposition (0, 15, 30 e 60 days before soybean seeding). The weed population and the characteristics of soybean growth and production were evaluated. The deposition of black oats and pearl millet straw provided reductions in weed density and dry mass, and this effect was more effective when the deposition occurred until 15 days prior to soybean seeding. The suppressor effect of black oats straw was more pronounced than that of pearl millet straw, regardless of the drying method, although the millet had a greater dry matter production. No significant differences were found between the drying methods and the straw effectiveness.
Black-oat and millet cover influence on weed community and soybean yield
Keywords: Glycine max L. Merrill; Straw; Yield; Avena strigosa; Glycine max; Pennisetum glaucum